2018
DOI: 10.18433/jpps30081
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring of Levetiracetam in Select Populations

Abstract: Routine TDM of levetiracetam is not recommended for all populations, however, it may be beneficial to maintain an individual therapeutic range in patients where the PK of LEV may be altered, such as in patients who are critically ill patients, pregnant, pediatrics or elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 38 publications
(84 reference statements)
1
24
0
Order By: Relevance
“…Headache was the second most common side effect reported in this study. Other studies have found that the similar observation [15]. Finally, with regard to whether participants believed Levetiracetam could harm or kill, majority of them were aware about the toxicity of Levetiracetam.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Headache was the second most common side effect reported in this study. Other studies have found that the similar observation [15]. Finally, with regard to whether participants believed Levetiracetam could harm or kill, majority of them were aware about the toxicity of Levetiracetam.…”
Section: Discussionsupporting
confidence: 66%
“…Levetiracetam is a broad-spectrum antiepileptic drug with a unique mechanism of action. AEDs are strong agents that can cause numerous adverse reactions and drug-drug interactions [13][14][15]. This survey is aimed to determine the usage, availability and knowledge of toxicity of Levetiracetam among the patients.…”
Section: Discussionmentioning
confidence: 99%
“…LEV exhibits first-order kinetics following a single dose and during long-term administration with excretion primarily through kidneys [ 4 ]. Half-life of LEV is 6–8 h in healthy adults, reaching steady states within 48 h [ 4 , 5 , 6 , 7 ]. Metabolism of LEV is not dependent on the hepatic cytochrome P450 system, whereas the acetamide group of plasma hydroxylase is involved [ 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In children with epilepsy, the half-life of LEV was shorter and clearance rates were higher than those in adults [ 17 ]. On the contrary, the half-life was longer and clearance rates were lower in elderly patients, compared to those in young adults and children [ 5 , 18 ]. In patients with renal impairment, LEV clearance was decreased in all ages [ 5 , 16 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation